Pengaruh Eq, Iklim, dan Kepemimpinan Kepala Madrasah terhadap Kinerja Guru - Diva Savitri; Elfi Yuliani Rochmah; Andhita Dessy Wulansari; Ahmadi Ahmadi (Excelencia: Journal of Islamic Education & Management, 2023)
This research is motivated by the teacher performance issue at MI Plus Al-Islam Dagangan Madiun. This issue is indicated by the fact that there are still approximately 35% of teachers who are incapable of properly controlling the class, as well as the lack of teacher sensitivity and commitment to students during the teaching and learning process. In addition, in terms of preparing lesson plans, several teachers have not fully prepared the lesson plans properly. This study aims to find out the significance of the influence of the Madrasah Principal's leadership, madrasah climate, and teacher’s Emotional Intelligence on teachers' performance in MI Plus Al-Islam Dagangan Madiun for the 2022/2023 Academic Year. This study uses a quantitative approach with ex post facto methods. The population is all teachers at MI Plus Al-Islam Dagangan Madiun, totaling 80 people. The sampling technique used is saturated samples. Meanwhile, the data analysis technique uses simple and multiple linear regression analysis. The results of the analysis show: the leadership of the Madrasah Principal, the climate of the madrasah, and the teacher's Emotional Intelligence have a significant effect on teachers' performance in MI Plus Al-Islam Dagangan Madiun for the 2022/2023 Academic Year, with around 55.1%.